An artificial Li-Al interphase layer on Li-B alloy for stable lithium-metal anode. (1st May 2019) - Zhong, Hai; Wu, Yuxuan; Ding, Fei; Sang, Lin; Mai, Yaohua
Abstract: Li-B alloy can be used as a lithium-metal anode, and this alloy maintains the entire structure of Li7 B6 constituents after the removal of free Li. In this study, a compact Li-Al layer which allows electron and ion transport to form in situ on the Li-B electrode was developed to solve the fundamental challenges of the Li-metal anode. Results of symmetric-cell tests show that the Li-Al layer coating on Li-B electrode can improve cyclic life over 1200 h at a current density of 0.2 mA cm −2, whereas bare Li-B electrode has stable cycles not exceeding 800 h. Results of scanning electron microscopy analysis demonstrate that Li deposition occurs beneath the Li-Al layer, and that the Li-Al alloy layer effectively reduces Li-metal corrosion and suppress the formation of Li dendrites. When matched with LiNi0.8 Co0.15 Al0.05 O2 cathode, the Li-B with Li-Al layer shows improved cycle stability and lower voltage difference than bare Li-B anode. Highlights: A flat and compact Li-Al layer formed in situ on the Li-B electrode. A Li-Al layer is a mixed ionic/electronic conductor for electron and ion transport. The lithium deposition occurs beneath the Li-Al layer. Li dendrites growth is inhibited and side reaction is reduced by the Li-Al layer.